Islamisasi Ilmu sebagai Jawaban atas Sekularisasi Pendidikan di Indonesia - Mardiati M; St. Nurhayati Ali; Nursia Nursia; Muh Iqbal Muhidin; Zulbina Zulbina (FKIP UNSULTRA, 2025)
The secularization of education is a global phenomenon that has influenced the Indonesian education system, characterized by the separation of religious values ​​from the process of developing knowledge. This condition has resulted in educational practices that emphasize cognitive and technical aspects, while ignoring spiritual, moral, and ethical dimensions. This article aims to analyze the concept of the Islamization of knowledge as an alternative educational paradigm capable of addressing the challenges of secularization. This research uses a qualitative approach with a literature study method of various relevant primary and secondary sources, such as books, journal articles, and educational policy documents. The results of the study indicate that the Islamization of knowledge is not intended as a rejection of modern science, but rather as an integrative effort to place knowledge within the framework of monotheistic values. This concept emphasizes the unity of knowledge, faith, and good deeds, so that education not only produces individuals who are intellectually intelligent but also have character and are morally responsible. In the context of Indonesian education, the Islamization of knowledge has the potential to become a philosophical foundation in curriculum development, learning processes, and national education goals that align with the religious values ​​of Indonesian society. Thus, the Islamization of knowledge can be understood as a conceptual and practical solution to address the secularization of education, as well as an effort to build a holistic and civilized education system.